Penanaman karakter sikap bersahabat melalui storytelling - Yunistianingsih Yunistianingsih; Itsnain Alfajri Husain (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
friendly attitude is needed by elementary school children to be able to liven up a fun atmosphere in learning. Even so, there was often an atmosphere that does not show the character of a friendly attitude. Storytelling is considered to be able to increase friendly attitudes. This study aims to determine whether the character of a friendly attitude can be improved through storytelling. This was a qualitative descriptive study. The primary data in this study came from two teachers and three students. Data were collected through interviews, observations, and documentation studies. Data were analyzed through data reduction, data display, verification, and conclusions. The results showed that the character of a friendly attitude can be improved through storytelling. Storytelling is able to break down potential conflicts. One of the obstacles in implementing this technique is that it requires the selection of an interesting theme. As a solution to the obstacles faced, preparation was needed in carrying out storytelling.